Construct Validity of the Brazilian Version of the Functional Activities Questionnaire - Rafael Tavares Jomar; Roberto Alves Lourenço; Claudia de Souza Lopes (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To investigate the construct validity of the Brazilian version of the Functional Activities Questionnaire (FAQ-BR), which measures the functional capacity of the elderly, based on an informant's report. METHODS: A cross-sectional study was performed with 525 non-hospitalized elderly and their respective informants. Pearson's and Kendall's tau correlation coefficients with a statistical significance level of < 0.05 were used to evaluate the correlation between the FAQ-BR score and sociodemographic and health condition variables. RESULTS: All correlations were compatible with the underlying theory, with a statistical significance (p value < 0.001): age (r = 0.522); income (r = - 0.148); years of schooling (r = - 0.191); living alone (r = - 0.175); self-rated health (r = - 0.149); chronic self-reported diseases (r = 0.125) and; cognitive impairment (r = 0.350). CONCLUSION: Although the FAQ-BR demonstrates construct validity, future complementary studies should be done to further measure elderly people's functional capacity, based on an informant's report.